2009
DOI: 10.1080/14764170902792199
|View full text |Cite
|
Sign up to set email alerts
|

Hair removal with a novel, low fluence, home-use intense pulsed light device

Abstract: In simulated consumer use, this home-use IPL demonstrated a significant, quantifiable and sustainable reduction in unwanted body and facial hair with minimal side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 16 publications
0
37
0
1
Order By: Relevance
“…These seven prospective studies were evaluated for efficacy and adverse effects and are summarized in Table 2. One study was categorized as a CT 7 and six as UCTs 8–13 . A total of 24 studies were excluded because they did not assess the efficacy of light‐based home use devices according to our a priori methodological criteria.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These seven prospective studies were evaluated for efficacy and adverse effects and are summarized in Table 2. One study was categorized as a CT 7 and six as UCTs 8–13 . A total of 24 studies were excluded because they did not assess the efficacy of light‐based home use devices according to our a priori methodological criteria.…”
Section: Resultsmentioning
confidence: 99%
“…All included trials evaluated short‐term (<6 months) hair reduction and one UCT 12 assessed long‐term hair reduction up to 12 months after treatment. Four of six short‐term studies 9–11,13 assessed the outcome at 3 months and two short‐term studies 7–8 evaluated outcome at 6 months after the final treatment. From Table 2 it is seen that the short‐term efficacy at 3 month follow‐up varied substantially, from 6% to 72% hair reduction (six studies), whereas more homogenous outcomes from 41% to 44% were reported at 6 month follow‐up (three studies).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations